Tracing the Theory of Hadith Quality in Kitab al-Jami' al-Sahih al-Sunan al-Tirmidzi - Baiquni Ach Baiquni (Al-Bukhari : Jurnal Ilmu Hadis, 2021)
This paper tries to describe some of imam al-Tirmidizi's views related to the theory of hadith quality found in the book al-Jami al-Şahih al-Sunan al-Tirmîdzi , this paper is a literature study with a descriptive approach that yields the conclusion that Imam al-Tirmîdzi has a different concept than the hadith expert in describing the hadith ṣahīh, hasan and dha’īf. In the case of ṣahīh hadith, the theory used by imam al-Tirmdizi is almost the same as other hadith experts i.e. hadith sahih is a hadith whose isith continues, Narrated by the 'adil and dhabīt, while in the theory of hasan hadith, Tirmidzi has a unique concept that divides hasan into three namely hasan ṣahīh (hadith hasan approaching ṣahīh), hasan (hadith that exists about hasan sahih and gharīb) and hasan gharīb is a hadith that is close to hadith dha’īf. Then, the theory of dha’īf by Imam al-Tirmîdzi is the same as other hadith scholars who do not meet ṣahīh and hasan and the connection of sanad is questioned.